Bali, Lombok & Nusa Tenggara 2024 - Exelby, Narina; Kaminski, Anna; Lempa, Sarah; Ver Berkmoes, Ryan (Lonely Planet guidebooks., 2024)
Lonely Planet Bali & Lombok is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Stand amongst the clouds on Gunung Rinjani, party all-night in Kuta, or experience the Gili Islands' phenomenal diving scene; all with your trusted travel companion.